PELAKSANAAN FUNGSIFUNGSI MANAJEMEN PENDIDIKAN ISLAM DALAM PEMBENTUKAN KARAKTER SANTRI DI MTS DMP DINIYYAH PUTERI PADANG PANJANG - Marlena Marlena (IAIN Batusangkar, 2016)
Implementation of Islamic Education Management Functions In the Building of Character Santri MTs DMP Diniyyah Puteri Padang Panjang. MTs DMP college Diniyyah Puteri one educational institution that has a focus on character education program, in addition to character education is through every subject is also infused through character education activities in schools. The focus of this study, namely: (1) Planning character education, (2) Organizing character education, (3) Implementation of character education, (4) Control and Evaluation of character education, and (5) Cultivation of character education . The purpose of this study are: (1) To describe the implementation of management functions in the application of Islamic education character education students in junior college DMP Puteri Padang diniyyah length, (2) To know the cultivation of character education in college DMP Diniyyah Puteri Padang Panjang.Results of this study are: ( 1 ) aspects of planning include: designing schools and boarding conditions are conducive, integrating designing curriculum and extracurricular activities , and conditioning classes , (2 ) aspects of organizing , all the components involved in pembentuka character of students, (3 ) aspects implementation , as well as PBM also at the time of self-development, at the time of the flag ceremony , super camp students, training super students, out bound, home stay, scientific studies in and outside the country, and others, (4 ) Control and Evaluation, pengontolan done by all of the existing components, while the evaluation is done by subject teachers or teacher concerned. Cultures that support the implementation of character education here is: a culture of honesty, cleanliness, sunnah prayers, trainings and extracurricular activities.Kata Kunci: fungsi-fungsi manajemen, pendidikan karakter